If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5 + -1X) + 2X = 0 (5 * 3 + -1X * 3) + 2X = 0 (15 + -3X) + 2X = 0 Combine like terms: -3X + 2X = -1X 15 + -1X = 0 Solving 15 + -1X = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -1X = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -1X = 0 + -15 -1X = 0 + -15 Combine like terms: 0 + -15 = -15 -1X = -15 Divide each side by '-1'. X = 15 Simplifying X = 15
| R-4=2r+3 | | 8*x=48 | | 12x-9=8x+37 | | 10x-60=90 | | 2b+8=-10-4b | | 8n-4+4=-3+4n+5n | | 65=273-x | | -14+6b+7-2b=1-5b | | 42=-x+7x-12 | | 174=68-x | | -3+5x=-7+1+6x-1 | | -80=-0.16x | | -y+125=191 | | -80=-0.16 | | 7(-3p+4)-5p=28 | | 192-v=3 | | -1.08+0.92= | | (5*x-3)+4=3 | | -5(6m-7)=5 | | 4(-3n+1)=64 | | -8x+30=62 | | 7(x+7)=7 | | X^3-225=0 | | log(4)(x)+log(8)(x^2)=3 | | 0.6r=-78 | | 8(7x-1)=-8 | | 10x+70=90 | | 5-6(x-3)=10 | | 11x+21=142 | | -2m-7=2m+5 | | (x^6)-(x^3)-(6)=0 | | -3(6+5k)-k=-34 |